Human dental stem cell derived transgene‐free iPSCs generate functional neurons via embryoid body‐mediated and direct induction methods. (17th January 2018) - El Ayachi, Ikbale; Zhang, Jun; Zou, Xiao‐Ying; Li, Dong; Yu, Zongdong; Wei, Wei; O'Connell, Kristen M.S.; Huang, George T.‐J.
Abstract: Induced pluripotent stem cells (iPSCs) give rise to neural stem/progenitor cells, serving as a good source for neural regeneration. Here, we established transgene‐free (TF) iPSCs from dental stem cells (DSCs) and determined their capacity to differentiate into functional neurons in vitro. Generated TF iPSCs from stem cells of apical papilla and dental pulp stem cells underwent two methods—embryoid body‐mediated and direct induction, to guide TF‐DSC iPSCs along with H9 or H9 Syn‐GFP (human embryonic stem cells) into functional neurons in vitro. Using the embryoid body‐mediated method, early stage neural markers PAX6, SOX1, and nestin were detected by immunocytofluorescence or reverse transcription‐real time polymerase chain reaction (RT‐qPCR). At late stage of neural induction measured at Weeks 7 and 9, the expression levels of neuron‐specific markers Nav1.6, Kv1.4, Kv4.2, synapsin, SNAP25, PSD95, GAD67, GAP43, and NSE varied between stem cells of apical papilla iPSCs and H9. For direct induction method, iPSCs were directly induced into neural stem/progenitor cells and guided to become neuron‐like cells. The direct method, while simpler, showed cell detachment and death during the differentiation process. At early stage, PAX6, SOX1 and nestin were detected. At late stage of differentiation, all five genes tested, nestin, βIII‐tubulin, neurofilament medium chain, GFAP, and Nav, were positive in many cells in cultures. Both differentiation methods led to neuron‐like cells in cultures exhibiting sodium and potassium currents, action potential, or spontaneous excitatory postsynaptic potential. Thus, TF‐DSC iPSCs are capable of undergoing guided neurogenic differentiation into functional neurons in vitro, thereby may serve as a cell source for neural regeneration.